A New Fractional Integral Inequality with Singularity and Its Application - Qiong-Xiang Kong; Xiao-Li Ding (Abstract and Applied Analysis)
We prove an integral inequality with singularity, which complements some known results. This inequality enables us to study the dependence of the solution on the initial condition to a fractional differential equation in the weighted space.